Revisiting the role of high‐energy Pacific events in the environmental and cultural history of Easter Island (Rapa Nui). Issue 3 (2nd May 2018) - Margalef, Olga; Álvarez‐Gómez, José A.; Pla‐Rabes, Sergi; Cañellas‐Boltà, Núria; Rull, Valentí; Sáez, Alberto; Geyer, Adelina; Peñuelas, Josep; Sardans, Jordi; Giralt, Santiago
Abstract : Pacific islands are spread over thousands of kilometres of the Pacific Basin and are characterised by similar ecological features but very diverse geologic origins, from steep volcanoes to flat coral atolls. Several climatic phases have been shared across the region within the last 1, 000 years. Numerous and abrupt societal and cultural changes during the same period have been described for islands separated by thousands of kilometres. Conspicuous societal changes have been exclusively attributed to the main climatic patterns (changes in precipitation and temperature). The possible role of tsunamis and the occurrence of large volcanic eruptions as regional societal modulators, however, have traditionally received little attention from archaeologists, mainly due to the difficulty of recognising them in the sedimentary and geomorphological records. We explore the potential influence of the most important high‐energy events in the Pacific on Polynesian societal changes, with a special focus on Easter Island. For example, the extreme Samalas eruption in AD 1257 may have been an indirect driver of the sudden population decline, land degradation and decreased food resources on many Pacific islands between AD 1250 and 1300, and the Kuwae eruption in AD 1450 may have triggered the synchronous end of long voyaging expeditions across the Pacific. Important palaeo‐tsunamis have had unquestionable impacts on coastal and seafaring societies. A direct effect of the main eruptions of the last millennia (AD 1257 and 1453) on Easter Island has not yet been identified by any record, but we have calculated the likelihood of destructive tsunamis with an estimated period of recurrence for large events of less than a century. This insight is new and needs to be taken into account to complement what we already know about Easter Island's cultural history and archaeological sites, especially those in vulnerable coastal locations.